Delivering an efficient and effective support group for patients with implantable cardioverter-defibrillators (ICDs): patient perspectives of key concerns and predictors of inclination to attend - Kathryn Murray; Kelly Buttigieg; Michelle Todd; Vicky McKechnie (BMC, 2021)
Abstract Background A subset of patients experience psychological distress following insertion of an implantable cardioverter-defibrillator (ICD) and ICD support groups are recommended, however access to these groups is limited. This study aimed: to gauge a better understanding of patients' key ICD-related concerns; to determine patient interest in a support group and topics deemed helpful to address in a support group; and to examine factors which affect patient inclination to attend. Methods One hundred and thirty nine patients completed the ICD Patient Concerns Questionnaire - Brief (ICDC-B) and a semi-structured survey. Non-parametric tests were used to examine associations and differences in the quantitative data. Qualitative data were analysed using thematic analysis. Results 42% of respondents said they would attend a support group and inclination to attend was associated with higher ICD concerns and a shorter time since implant. Topics considered important to address in a group were information about heart conditions and devices, the impact of an ICD on daily life and coping with fear of shocks. Conclusion We concluded that there is interest in further support amongst many patients and that ICD support groups may be delivered efficiently by targeting patients who have higher levels of ICD concerns and within the first few years after implant.